5-aminolevulinic acid induced photodynamic reactions in diagnosis and therapy for female lower genital tract diseases - Chen, Yuqing; Guo, Peng; Chen, Lihong; He, Dalin (Frontiers in Medicine, 2024)
Research Interest: bladder cancer, prostate cancer invasion and metastasis mechanism; tumor related gene screening and identification; standardized treatment and other clinical researches Credits: won 1 first prize of National Science and Technology Progress and 5 Science and technology Progress Awards of Shaanxi Province; edited and published Urogenital Oncology; published 123 papers in international journals; applied for 5 new utility patents (authorized) and 3 invention patents (authorized) as the first applicant